Association of body composition and age at menarche in girls and adolescents in the Brazilian Legal Amazon - Ivanice Fernandes Barcellos Gemelli; Edson dos Santos Farias; Poli Mara Spritzer (Elsevier, 2020)
Objective: To analyze the association between age at menarche and variables of body composition in girls from the Northern region of Brazil, the Brazilian Legal Amazon. Method: The sample was composed of 926 school girls, aged between 8 and 18 years, divided into two groups, those who had (G1; n = 727; 72.5%) and had not undergone menarche (G2; n = 199; 21.5%), from public and private schools, using the stratified random proportional sampling technique. Weight, fat weight, muscle weight, and body mass index were measured using bioimpedance analysis. Body height was measured using a stadiometer. Age at menarche was obtained using the conventional method. For the evaluation of sexual maturation, self-assessment was performed according to criteria described by Tanner. Results: The highest cumulative distribution of menarche was found at age 11, and presented significant differences between G1 and G2 at ages 11 and 12 years in all variables of body composition, except body mass index Z-score. Fat and muscle mass were associated with age at menarche. Conclusion: The present results support the notion of menarche anticipation in girls from Brazilian Amazon and its association with body composition. Further studies are needed to investigate the influence of other possible factors that may interfere with the time of growth spurt, thus determining the timing of puberty in these girls in comparison to other regions of Brazil. Resumo: Objetivo: Analisar a associação entre idade da menarca e variáveis da composição corporal em meninas na região norte do Brasil, a Amazônia brasileira. Método: A amostra foi composta por 926 meninas em idade escolar, entre 8 e 18 anos, divididas em dois grupos, com presença de menarca (G1), n = 727 (72,5%) e ausência (G2) n = 199 (21,5%), provenientes de escolas públicas e privadas, com a técnica de amostragem aleatória estratificada proporcional. Peso, massa de gordura, massa muscular e índice de massa corporal foram medidos através da análise de bioimpedância. A altura foi medida com um estadiômetro. A idade da menarca foi obtida pelo método status quo. Para a avaliação da maturação sexual, a autoavaliação foi realizada de acordo com os critérios descritos por Tanner. Resultados: A maior distribuição cumulativa da menarca foi encontrada aos 11 anos, e apresentou diferenças significativas entre a presença e ausência de menarca aos 11 e 12 anos em todas as variáveis de composição corporal, exceto o escore-z do índice de massa corporal. Massa de gordura e massa muscular foram associadas com a idade da menarca. Conclusão: Os resultados apresentados corroboram a antecipação da menarca em meninas da Amazônia brasileira e sua associação com a composição corporal. Mais estudos são necessários para investigar a influência de outros possíveis fatores que podem interferir na época do estirão de crescimento e determinar, assim, a ocorrência da puberdade em meninas amazônicas em comparação com as de outras regiões do Brasil. Keywords: Menarche, Body composition, Body height, Palavras-chave: Menarca, Composição corporal, Altura corporal